Efektivitas Model Pembelajaran RADEC dalam Meningkatkan Kemampuan Komunikasi Matematika - Ulum, Achmad Miftachul; Sari, Sulistya Umie Ruhmana (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2025)
Mathematical communication ability is a key component of overall mathematical proficiency. Enhancing this skill can be achieved through the application of an effective learning model. The RADEC learning model serves as a promising method to boost students’ mathematical communication capabilities. This study seeks to examine the differences in mathematical communication skills between an experimental group taught using the RADEC model and a control group, as well as to evaluate the model’s effectiveness in fostering these skills. Employing a quantitative approach with a true experimental design and a pretest-posttest control group setup, the research was carried out in a school located in Mojokerto City, involving class XE1 as the experimental group and XE2 as the control. Data were gathered via tests and observations, utilizing instruments such as mathematical communication skill assessments and observation checklists for RADEC implementation. The data were analyzed through descriptive and inferential statistical methods. Findings indicated a notable difference between the experimental and control groups, with mean scores of 31.4 and 21.3 respectively. The Mann-Whitney U test showed a significance value of 0.000 (p < 0.05), confirming the difference was statistically significant. Furthermore, the N-Gain analysis revealed that the improvement in mathematical communication skills was moderate. In summary, the RADEC learning model effectively enhances students’ ability to communicate mathematically.